On the automorphism groups of Steiner triple systems constructed by the Skolem method - Mwambene, Eric; Vodah, Sunday (Utilitas Mathematica, 2018)
We determine the automorphism group of Steiner triple system of order v = 1 (mod 6), constructed by the Skolem method using an even order quasigroup. By determining the automorphism group of Skolem quasigroup, it may become evident why the full automorphism group of this design inherits the rigidity of the quasigroup used in its construction. © 2018 Utilitas Mathematica Publishing Inc. All rights reserved.